The Role of Vision 2030’s Progressive Agency in the Common Interactive Structural between Gender in the Saudi Business Environment:A Sociological Analysis Using the Theory of Conflicting Rules (TCR) - Alshahrani, Abdullah (The Arab Journal of Administration, 2025)
With the launch of Saudi Arabia’s Vision 2030, business organizations are entering into transformational processes. Vision 2030 is a progressive, authoritarian agency that seeks to reinvest Saudi manpower in the business, economic and service sectors in a way that achieves the optimal utilization of human competencies and capabilities. Therefore, the study sought to identify the role of the progressive agency of the Kingdom of Saudi Arabia’s Vision 2030 in the reality of the rules of common interactive structure - the common sense - organizing informal oral structural rules (dynamic, spiritual, cultural intellectual). Using a mixed method (qualitative/quantitative) approach that is dominated by the qualitative approach according to the ethnographic method. The qualitative method was used to explore the existential ontological and axiological dimensions of the research phenomenon, while the quantitative method was used in the epistemological dimension, relying on the theory of conflicting rules (TCR). (Alshahrani et al., 2024) was used to construct an organizational scale derived from the first hypotheses of the theory of conflicting rules (TCR), in which the responses of (417) male and female employees working in the Saudi mixed business environment were taken, and the study showed in its ontological dimension three initial dimensions of the form of the common interactive structure - the common sense - organizing informal oral interactions in the Saudi mixed business environment, namely (oral interactions, self-trust and mutual trust, conflict between rules of upbringing behavior, and the rules of the new business environment). While the epistemological dimension showed that there is a direct relationship between the independent variable (authoritarian progressive agency of vision 2030) and the dependent variable (common interactive structure), i.e. the more progressive the authoritarian progressive agency, the greater the common interactive structure, as there is a statistically significant role for the authoritarian progressive agency in predicting the common interactive structure according to the regression model, This is quantitative evidence that the more authoritarian progressive agency, the more rational the common interactive structure. As for the ecological dimension, the study believes that there is a potential positive impact of organizational values (objective, subjective) resulting from the empowerment of women and their increased participation in the mixed Saudi business environment.